The role of notch tip shape and radius on deformation mechanisms of 12Cr1MoV steel under impact loading. Part 2. Influence of strain localization on fracture and numeric simulations - Panin S. V. Sergey Viktorovich; Maruschak P. O. Pavel Orestovich; Vlasov I. V. Ilya Viktorovich; Moiseenko D. D. Dmitry Davidovich; Maksimov P. V. Pavel Vasiljevich; Berto F. Filippo; Bishchak R. T. Roman Teodorovich; Vinogradov A. Yu. Aleksey Yurjevich (2017, 2017)
Title screen